ANALISIS KINERJA PEGAWAI DALAM PELAYANAN PENERBITAN SURAT IZIN USAHA PERDAGANGAN (SIUP) PADA BADAN PELAYANAN TERPADU DAN PENANAMAN MODAL KOTA PEKANBARU - Novika Ningsih; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study was motivated by the phenomenon that the publishing service of Trading BusinessLicense (SIUP) is not maximized. Proved by the license issuance is not completed on time.Though ownership License is required to be owned businesses to a business carried on havinga strong legal basis in accordance with the provisions of the Indonesian state in order for theeffort that has been initiated can be maintained in existence and continuance arecharacterized by the presence of the tangible elements of the legality of the ownership of thebusiness license. Then the lack of the number of employees in the management of licenseissuance also resulted in a lack of quality of service of the employees in this license issuance.The formulation of the problem is How employee performance in service of publishing TradingBusiness License (SIUP) in the Integrated Service Agency and Investment of Pekanbaru City?And what factors could obstruct employee performance in service publishing Trading BusinessLicense (SIUP) in the Integrated Service Agency and Investment of Pekanbaru City?. This studyaims to investigate the performance of employees in a publishing service of Trading BusinessLicense (SIUP) and to determine the factors that obstruct employee performance in servicepublishing Trading Business License (SIUP). The benefits of this research is to develop andapply the theory of public policy obtained by the author during the lectures and during theconduct of the study as well as an input for the Integrated Service Agency and Investment ofPekanbaru City and as reference material for other researchers to discuss the same issue.This study used a qualitative approach and type of research is descriptive. Type and source ofdata consists of primary data and secondary data. The data was collected by using observation,interview and documentation.Keyword: Performance, Public Service